The Phytoplankton Taxon-Dependent Oil Response and Its Microbiome: Correlation but Not Causation - Severin, Tatiana; Erdner, Deana L. (Frontiers in Microbiology, 2019)
Phytoplankton strongly interact with their associated bacteria, both attached (PA) and free-living (FL), and bacterial community structures can be specific to phytoplankton species. Similarly, responses to environmental stressors can vary by taxon, as exemplified by observed shifts in phytoplankton community structure from diatoms to phytoflagellates after the Deepwater Horizon oil spill. Here, we assess the extent to which associated bacteria influence the phytoplankton taxon-specific oil response by exposing xenic and axenic strains of three phytoplankton species to oil and/or dispersant. The dinoflagellates Amphidinium carterae and Peridinium sociale, and the diatom Skeletonema sp., all harbored significantly distinct bacterial communities that reflected their host oil response. Oil degrading bacteria were detected in both PA and FL communities of the oil resistant dinoflagellates, but their FL bacteria were more efficient in lipid hydrolysis, a proxy for oil degradation capability. Inversely, the growth rate and photosynthetic parameters of the diatom Skeletonema sp. was the most impacted by dispersed oil compared to the dinoflagellates, and oil-degrading bacteria were not significantly associated to its microbiome, even in the dispersed oil treatment. Moreover, the FL bacteria of Skeletonema did not show significant oil degradation. Yet, the lack of consistent significant differences in growth or photosynthetic parameters between the xenic and axenic cultures after oil exposure suggest that, physiologically, the associated bacteria do not modify the phytoplankton oil response. Instead, both oil resistance and phycosphere composition appear to be species-specific characteristics that are not causally linked. This study explores one aspect of what is undoubtedly a complex suite of interactions between phytoplankton and their associated bacteria; future analyses would benefit from studies of genes and metabolites that mediate algal-bacterial exchanges.